Investigation of the Antioxidant and Total Phenolic Substance of Fomes fomentarius and Ganoderma applanatum Mushrooms Showing Therapeutic Properties - Karadeniz, Mertcan; Bakır, Temel Kan; Ünal, Sabri (Bilge International Journal of Science and Technology Research, 2024)
Fomes fomentarius (Ffo) and Ganoderma applanatum (Gap), which are mushroom species used in traditional medicine in Far East Asia, are widely found in our country and attract great attention with their antioxidant properties. In this study, the antioxidant activities of these mushrooms grown in our country were examined spectrophotometrically using the DPPH method. The results were expressed as percent inhibition and also the IC50 values of the fungal samples were calculated using concentration equations. IC50 values for Ganoderma applanatum and Fomes fomentarius were found to be 0.515 and 0.463 mg/mL, respectively. Additionally, total phenolic substances were analyzed by the Folin-Ciocalteu Method. Phenol content in methanolic extracts expressed in gallic acid equivalents (GAE) was found to be 8,447 and 10,300 mg/L for Ganoderma applanatum and Fomes fomentarius, respectively. In this study, it was determined that both types of mushrooms are valuable in terms of both their phenolic content and antioxidant properties.
Keywords: Orman Biyoçeşitliliği; Forestry Sciences (Other); Fomes fomentarius (Ffo); Ganoderma applanatum (Gap); Total phenolic substances; DPPH method; Forest Biodiversity; Ormancılık (Diğer); 3. Good health